Another Look at Airport Congestion Pricing - Morrison, Steven A; Winston, Clifford (American Economic Review, 2007)
We study alternate approaches to implement congestion pricing at US airports. Conventional formulations toll all aircraft without determining whether a plane operated by a given airline delays other planes that it operates or planes operated by other airlines. Recent work points out optimal pricing calls for carriers to be charged only for the delay they impose on other airlines. We find a small difference between the net benefits generated by the two congestion-pricing policies because the bulk of airport delays are not internalized and because the efficiency loss from pricing internalized congestion is small. (JEL L11, L93, R41)